ThunderDome: Discovering Upload Constraints Using Decentralized Bandwidth Tournaments - Douceur, John (JD); Mickens, James; Moscibroda, Thomas; Panigrahi, Debmalya (CoNext 2009: 5th ACM International Conference on Emerging Networking Experiments and Technologies, Rome, Italy, 2009)
ThunderDome is a system for collaboratively measuring upload bandwidths in ad-hoc peer-to-peer systems. It works by scheduling bandwidth probes between pairs of hosts, wherein each pairwise exchange reveals the upload constraint of one participant. Using the abstraction of bandwidth tournaments, unresolved hosts are successively paired with each other until every peer knows its upload bandwidth. To recover from measurement errors that corrupt its tournament schedule, ThunderDome aggregates multiple probe results for each host, avoiding pathological bandwidth estimations that would otherwise occur in systems with heterogeneous bandwidth distributions. For scalability, the coordination of probes is distributed across the hosts. Simulations on empirical and analytic bandwidth distributions—validated with wide-area PlanetLab experiments—show that ThunderDome efficiently yields upload bandwidth estimates that are robust to measurement error.